Anatomic Assessment of the Limits of an Endoscopically Assisted Retrolabyrinthine Approach to the Internal Auditory Canal - Muelleman, Thomas J.; Maxwell, Anne K.; Peng, Kevin A.; Brackmann, Derald E.; Lekovic, Gregory P.; Mehta, Gautam U. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Data regarding the surgical advantages and anatomic constraints of a hearing-preserving endoscopic-assisted retrolabyrinthine approach to the IAC are scarce. This study aimed to define the minimum amount of retrosigmoid dural exposure necessary for endoscopic exposure of the IAC and the surgical freedom of motion afforded by this approach.Methods Presigmoid retrolabyrinthine approaches were performed on fresh cadaveric heads. The IAC was exposed under endoscopic guidance. The retrosigmoid posterior fossa dura was decompressed until the fundus of the IAC was exposed. Surgical freedom of motion at the fundus was calculated after both retrolabyrinthine and translabyrinthine approaches.Results The IAC was entirely exposed in nine specimens with a median length of 12 mm (range: 10–13 mm). Complete IAC exposure could be achieved with 1 cm of retrosigmoid dural exposure in eight of nine mastoids. For the retrolabyrinthine approach, the median anterior–posterior surgical freedom was 13 degrees (range: 6–23 degrees) compared with 46 degrees (range: 36–53 degrees) for the translabyrinthine approach (p = 0.014). For the retrolabyrinthine approach, the median superior–inferior surgical freedom was 40 degrees (range 33–46 degrees) compared with 47 degrees (range: 42–51 degrees) for the translabyrinthine approach (p = 0.022).Conclusion Using endoscopic assistance, the retrolabyrinthine approach can expose the entire IAC. We recommend at least 1.5 cm of retrosigmoid posterior fossa dura exposure for this approach. Although this strategy provides significantly less instrument freedom of motion in both the horizontal and vertical axes than the translabyrinthine approach, it may be appropriate for carefully selected patients with intact hearing and small-to–medium sized tumors involving the IAC.
Keywords: endoscopic; internal auditory canal; retrolabyrinthine; vestibular schwannoma